2014
DOI: 10.1097/opx.0000000000000401
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Nerve Fiber Layer Configuration in Eyes with Epiretinal Membrane

Abstract: The configurations of the ONH and peripapillary RNFL in eyes with ERM were different from those in fellow eyes. The characteristic configurations of RNFL such as small peak angle and temporal quadrant thickening may be considered when evaluating parameters as measured by spectral domain optical coherence tomography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 29 publications
5
19
1
Order By: Relevance
“…This horizontal long structure is consistent with the form of the nerve fiber layer, the temporal fibers are dispersed widely, and a small percentage of arcuate fibers are dispersed horizontally. 16 In the present study, the ONL-B is more evident in ERM patients, the average axis was 2 degrees from the horizontal line, and 90% of ERM patients showed an axis within ± 45 degrees, which may be due to the ERM contraction direction. Our colleague recently reported that the vertical retinal displacement was greater than the horizontal retinal displacement, as assessed by measuring the position of the retinal vessels in ERM patients17, which indicates that retinal morphology is likely to deform to be horizontally long with ERM vertical contraction.…”
Section: Discussionsupporting
confidence: 44%
“…This horizontal long structure is consistent with the form of the nerve fiber layer, the temporal fibers are dispersed widely, and a small percentage of arcuate fibers are dispersed horizontally. 16 In the present study, the ONL-B is more evident in ERM patients, the average axis was 2 degrees from the horizontal line, and 90% of ERM patients showed an axis within ± 45 degrees, which may be due to the ERM contraction direction. Our colleague recently reported that the vertical retinal displacement was greater than the horizontal retinal displacement, as assessed by measuring the position of the retinal vessels in ERM patients17, which indicates that retinal morphology is likely to deform to be horizontally long with ERM vertical contraction.…”
Section: Discussionsupporting
confidence: 44%
“…This horizontal long structure is consistent with the form of the nerve fiber layer, the temporal fibers are dispersed widely, and a small percentage of arcuate fibers are dispersed horizontally. 16 In the present study, the ONL-B is more evident in ERM patients, the average axis was 2 degrees from the horizontal line, and 90% of ERM patients showed an axis within ± 45 degrees, which may be due to the ERM contraction direction. Our colleague recently reported that the vertical retinal displacement was greater than the horizontal retinal displacement, as assessed by measuring the position of the retinal vessels in ERM patients 17 , which indicates that retinal morphology is likely to deform to be horizontally long with ERM vertical contraction.…”
Section: Discussionsupporting
confidence: 44%
“…This horizontal long structure is consistent with the form of the nerve fiber layer, the temporal fibers are dispersed widely, and a small percentage of arcuate fibers are dispersed horizontally. 16 In the present study, the ONL-B is more evident in ERM patients, the average axis was 2 degrees from the horizontal line, and 90% of ERM patients showed an axis within ±45 degrees, which may be due to the ERM contraction direction. Our colleague recently reported that the vertical retinal displacement was greater than the horizontal retinal displacement, as assessed by measuring the position of the retinal vascular in ERM patients 17 , which indicates that retinal morphology is likely to deform to be horizontally long with ERM vertical contraction.…”
Section: Discussionsupporting
confidence: 44%